Desarrollo de la Creatividad a Través del Método de Pensamiento Creativo (2017)
Development of Creativity through the creative thinking method for eighth grade students, Colegio Colombo Florida Bilingüe, was born from the need to promote interest in creative development in the educational community. Artistic and cultural education stimulates cognitive and sensory expression skills, necessary for good personal, academic and social development.